Peran Guru Tuo di Madrasah Tarbiyah Islamiyah Canduang dalam Mentransformasikan Nilai-nilai Moderasi Beragama kepada Santri - Perista, Wiana; Rivauzi, Ahmad (Lembaga Yasin AlSys, 2024)
Teachers are the key to the educational process. No matter how good the curriculum and educational institutions are, teachers are an important element because of their position as subjects who transfer knowledge to students, including teachers in Islamic boarding schools. This research will answer the question of how guru tuo transform the values of religious moderation to students and how these values are maintained. This field research was conducted at Madrasah Tarbiyah Islamiyah Canduang (MTI Canduang), using qualitative methods and a phenomenological approach. The results of the research show that the guru tuo at MTI Canduang actually understand the values of religious moderation, just in different terms. Understanding of religious moderation was obtained from books taught at MTI Canduang and thoughts inherited from Sheikh Sulaiman Arrasuli. In this way, the guru tuo easily transforms the values of religious moderation to the students which radiates from the guru tuo role as an inspirer, informer, motivator and demonstrator. Then the guru tuo strategy in maintaining the values of religious moderation is carried out by playing the role of corrector and supervisor.